Introduction: Missing Persons and Hidden Heritages in European Lace Making. (2nd January 2020) - Botticello, Julie; Fisher, Tom
Abstract: This introduction highlights the connections and continuities between the articles in this special issue around the hidden aspects underpinning design and labor in the lace trade, over the period of the industrial revolution to the mid 20th century, across England, Belgium, and France. The papers draw on archival records, which include not only traditional text-based accounts, textile samples, and pattern designs, but also business records and songs, to uncover hidden information about processes, experiences, and labor, in the perpetuation of the lace trade over the period. "Missing Persons and Hidden Heritages in European Lace Making" demonstrates that examining these records will uncover the contributions and losses incurred by a range of hidden hands, bodies, and minds.